Technological Revolutions and Financial Capital: The Dynamics of Bubbles and Golden Ages - and Perez, Carlota (Edward Elgar Publishing Ltd, 2003)
Technological Revolutions and Financial Capital presents a novel interpretation of the good and bad times in the economy, taking a long-term perspective and linking technology and finance in an original and convincing way. Carlota Perez draws upon Schumpeter's theories of the clustering of innovations to explain why each technological revolution gives rise to a paradigm shift and a 'New Economy' and how these 'opportunity explosions', focused on specific industries, also lead to the recurrence of financial bubbles and crises. These findings are illustrated with examples from the past two centuries: the industrial revolution, the age of steam and railways, the age of steel and electricity, the emergence of mass production and automobiles, and the current information revolution/knowledge society. By analyzing the changing relationship between finance capital and production capital during the emergence, diffusion and assimilation of new technologies throughout the global economic system, this seminal book sheds new light on some of the most pressing economic problems of today. A bold interpretation of how the changing relationship between technological advances and financial capital shapes the patterns of economic cycles, this path-breaking book will provide essential insights for business leaders, policymakers, academics and others concerned with managing change in the world economy.